Understanding the endorsement of wife beating in Ghana: evidence of the 2014 Ghana demographic and health survey - Kwamena Sekyi Dickson; Edward Kwabena Ameyaw; Eugene Kofuor Maafo Darteh (BMC, 2020)
Abstract Background Domestic violence (DV) has become a global burden. The high occurrence of intimate partner violence (IPV) across the globe has implications for the socioeconomic wellbeing and health of children and women. Methods Data for the study was from the 2014 Ghana Demographic and Health Survey (GDHS). The association between approval of wife-beating and background characteristics of women was examined by the use of a Binary Logistic Regression model. Results A higher proportion of respondents were from urban areas (53.7 and 52.2% women and men respectively). The ages of women ranged from 15 to 49 (mean = 30, SD = 9.7) whilst the age range of men was 15-59 (mean = 32, SD = 12.5). Twenty-four percent of the men and 23% of the women were within the richest wealth category. The results showed that few women (6.3%) and men (11.8%) had attained higher education. Both women (AOR = 1.3; CI = 1.01-1.24) and men (AOR = 2.2; CI = 1.72-2.76) aged 15-24 had higher odds of approving wife-beating than those aged 35-49 (reference category). Poorest women (AOR = 2.7; CI = 2.14-3.38) and men (AOR = 1.7; CI = 1.11-2.69) alike had higher odds of approving wife-beating, as compared with those in the richest wealth status (reference category). As compared to research participants with higher/tertiary education, both women (AOR = 5.1; CI = 3.52-7.51) and men (AOR = 4.2; CI = 2.37-7.16) without any formal education were found to be at higher odds to approve wife-beating; however, this observation seems to decline as one's educational status advances. Conclusion Age, wealth status, level of education, frequency of listening to radio, frequency of reading newspaper/magazine, frequency of watching television, ethnicity, and religion were found to be significantly associated with Ghanaian men and women's approval of wife-beating. Policies, interventions, and campaigns must target Ghanaians without formal education and young adults on the need to uphold human rights in order to dissuade them from endorsing intimate partner violence. Mass media has also proven to be a protective factor against domestic violence approval and, as such, much progress can be made if utilised by human rights activists, especially through radio, magazine and television broadcasting.